Microridge-like structures anchor motile cilia - Takayuki Yasunaga; Johannes Wiegel; Max D. Bergen; Martin Helmstädter; Daniel Epting; Andrea Paolini; Özgün Çiçek; Gerald Radziwill; Christina Engel; Thomas Brox; Olaf Ronneberger; Peter Walentek; et al. (Nature Communications)
Abstract Several tissues contain cells with multiple motile cilia that generate a fluid or particle flow to support development and organ functions; defective motility causes human disease. Developmental cues orient motile cilia, but how cilia are locked into their final position to maintain a directional flow is not understood. Here we find that the actin cytoskeleton is highly dynamic during early development of multiciliated cells (MCCs). While apical actin bundles become increasingly more static, subapical actin filaments are nucleated from the distal tip of ciliary rootlets. Anchorage of these subapical actin filaments requires the presence of microridge-like structures formed during MCC development, and the activity of Nonmuscle Myosin II. Optogenetic manipulation of Ezrin, a core component of the microridge actin-anchoring complex, or inhibition of Myosin Light Chain Kinase interfere with rootlet anchorage and orientation. These observations identify microridge-like structures as an essential component of basal body rootlet anchoring in MCCs.